Female cyclists perceived effects and experiences of the menstrual cycle on training and performance - Louise Burnie; Paul Ansdell; Georgia Allen-Baker; Elisa Pastorio; Kirsty M. Hicks; Neil Heron; Natalie Brown (PLoS ONE, 2026)
The aim of this study was: (1) to understand female cyclist’s experiences and perceptions of the menstrual cycle (MC) on training and competition performance, and (2) to explore female cyclist’s comfort in having conversations relating to the MC with coaches and support staff. Twenty competitive female cyclists (age 35.1 ± 7.7 yrs, cycling for 11.9 ± 7.4 yrs, 3 elite, 7 sub-elite and 10 club cyclists) were interviewed using an open-ended, semi-structured approach. An inductive thematic analysis was conducted. Female cyclists’ experiences and perceptions of the MC on training and competition performance were wide ranging with participants reporting a range of MC symptoms that varied in severity and timing in the MC. 45% of the cyclists had experienced irregular MCs either currently or in the past with participants suggesting possible causes may be due to low body weight and insufficient energy intake to support training. 73% of the participants spoke to their coach about their MC, but typically this was limited to a note on their training programme that they started their period, or a brief mention of how they are feeling. Participants highlighted the positive influence of elite athletes talking about their MCs in terms of accepting the influence of MC on performance and improving openness of conversation. Most participants said they lacked knowledge about the MC and how to manage MC related symptoms. The findings highlight the need for improved education on the MC in sport for cyclists and coaches to improve performance and athlete health and wellbeing.